⎩ ⎨ ⎧ x 3 + 1 − x y 2 − y 2 = 0 y 3 + 1 − y x 2 − x 2 = 0
Find the number of pairs of real solutions ( x , y ) that satisfy the system of equations above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Usually when the equations are symmetric, we are tempted to make x = y . However, this is just one of the possibilities. What you should do, is to take the difference and factor out the ( x − y ) term as demonstrated above.
Problem Loading...
Note Loading...
Set Loading...
( x 3 + 1 − x y 2 − y 2 ) − ( y 3 + 1 − y x 2 − x 2 ) = 0 x 3 − y 3 − x y 2 + y x 2 − y 2 + x 2 = 0 Factorizing,we get ( x − y ) ( x + y ) ( x + y + 1 ) = 0 .Now we have 3 cases: Case 1: x = y ⟹ ( y ) 3 + 1 − ( y ) ( y 2 ) − y 2 = 0 ⟹ y 2 = 1 ⟹ y = 1 or y = − 1 y = 1 gives ( x , y ) = ( 1 , 1 ) while y = − 1 gives ( x , y ) = ( − 1 , − 1 ) Case 2: x = − y ⟹ ( − y ) 3 + 1 − ( − y ) y 2 − y 2 = 0 ⟹ y 2 = 1 ⟹ y = 1 or y = − 1 y = 1 gives ( x , y ) = ( − 1 , 1 ) while y = − 1 gives ( x , y ) = ( 1 , − 1 ) Case 3: x = − 1 − y ⟹ ( − 1 − y ) 3 + 1 − ( − 1 − y ) y 2 − y 2 = 0 ⟹ − 3 y 2 − 3 y = 0 ⟹ − 3 y ( y + 1 ) = 0 The case y = 0 gives ( x , y ) = ( − 1 , 0 ) while the case y = − 1 gives ( x , y ) = ( 0 , − 1 ) .
All the 6 pairs we have found satisfy both equations.Hence the answer is 6 .